Effects of compression on muscle tissue oxygenation at the onset of exercise - Coza, A.; Dunn, J. F.; Anderson, B.; Nigg, B. M. (The Journal of Strength and Conditioning Research, 2012)
The effects of compression on gastrocnemius medialis muscle oxygenation and hemodynamics during a short-term dynamic exercise was investigated in a sample of 15 male subjects (mean ± SD; age 25.8 ± 4.9 years; mass 70.6 ± 4.3 kg). Elastic compression sleeves were used to apply multiple levels of compression to the calf muscles during exercise, and noncompressive garments were used for the control condition. Tissue hemoglobin oxygen saturation was measured as the relative "tissue oxygen index" (TOI) with a near-infrared spectrometer. The recovery of TOI during exercise was determined from the slope of oxygenation recovery in a nonoccluded situation. The TOI recovery rate during the first 2 minutes of the exercise was 24% higher (p = 0.042) for the compression condition than for the control condition. A significant correlation (r = 0.61, p = 0.012) between the level of compression and the tissue oxygenation recovery during exercise was observed. Muscle energy use was determined from the rate of decline of TOI immediately upon arterial occlusion during early exercise. Muscle energy use measured during the occluded situation was not significantly influenced by compression. Based on these results, it was concluded that compression induced changes in tissue blood flow and perfusion appear to result in improved oxygenation during short-term exercise. Assuming that increased muscle oxygen availability positively influences performance, compression of muscles may enhance performance especially in sports that require repeated short bouts of exercise.